Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1097/acm.0000000000002715
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Shared Decision-Making Behaviors During Inpatient Rounds: A Multimodal Educational Intervention

Abstract: Purpose To estimate the effectiveness of a multimodal educational intervention to increase use of shared decision-making (SDM) behaviors by inpatient pediatric and internal medicine hospitalists and trainees at teaching hospitals at Stanford University and the University of California, San Francisco. Method The 8-week Patient Engagement Project Study intervention, delivered at four services between November 2014 and January 2015, included workshops, cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Unlike providers, who understood the process of SDM to be what is defined in the literature 1 and highlighted in SDM assessment tools [25][26][27] as an interactive and iterative approach, the majority of the parents, including both those with CMC and those with previously healthy children, instead identified the importance of providers actively listening and effectively communicating the medical condition and options. This research builds on the research of Blankenburg et al 20 and Harman et al, 21 who found a difference in parent and provider perceptions of SDM but did not identify the missing components. There was also the provider assumption that parents of CMC have more experience and knowledge in their child' s medical condition, making it easier to participate in SDM with this population.…”
Section: Theme 2: Providers Assume Sdm Is Easier With Parents Of Cmc Because Of Their Experiences and Knowledgementioning
confidence: 97%
See 1 more Smart Citation
“…Unlike providers, who understood the process of SDM to be what is defined in the literature 1 and highlighted in SDM assessment tools [25][26][27] as an interactive and iterative approach, the majority of the parents, including both those with CMC and those with previously healthy children, instead identified the importance of providers actively listening and effectively communicating the medical condition and options. This research builds on the research of Blankenburg et al 20 and Harman et al, 21 who found a difference in parent and provider perceptions of SDM but did not identify the missing components. There was also the provider assumption that parents of CMC have more experience and knowledge in their child' s medical condition, making it easier to participate in SDM with this population.…”
Section: Theme 2: Providers Assume Sdm Is Easier With Parents Of Cmc Because Of Their Experiences and Knowledgementioning
confidence: 97%
“…[14][15][16][17] In previous studies, researchers have found that patient perceptions of shared decisions differ from physician perceptions of SDM. 18,19 Blankenburg et al 20 and Harman et al 21 noticed a difference in parent and provider perceptions on inpatient rounds but did not identify the reason why. Given what little is known about how to optimize SDM during a child' s hospitalization, the objective of our study was to describe parents' and their providers' perspectives on SDM during the hospitalization of their children, including facilitators and barriers, and explore differences between parents of CMC and parents of children with no chronic conditions.…”
mentioning
confidence: 99%
“…ese English translations are not up to the standard, and the meaning is relatively vague [12]. After the students translate the exercises, the translation often deviates from the original meaning [13]. Students know how to translate, but they cannot express their inner thoughts correctly.…”
Section: Current Situation Of Traditional English Translationmentioning
confidence: 99%
“…39,41 In the post-graduate stage (post-licensure) SDM training is delivered in various methods and ways of delivery. Harman et al 42 developed a training program to improve the physicians' behavior towards SDM, which was conducted when doing rounds of inpatients. The training program included Patient Engagement Project (PEP) workshop on SDM, followed with a campaign of using SDM in the form of posters, pocket cards, and electronic messages as a reinforcement of previously received SDM material.…”
Section: Learning Sdm Dan Ip-sdmmentioning
confidence: 99%